VD_FINDINFO Jug / 2018 / 169 vom 9. November 2017 - VD Tribunal cantonal (2017)
CHANTAGE, TENTATIVEDROIT PÉNAL, RECEL, SURSIS À L'EXÉCUTION DE LA PEINE | 160 ch. 1 CP, 22 ad 156 ch. 1 CP, 42 CP, 47 CP